30 years of justice system reform and economic rationality - Sumar, Oscar (2024)
The Peruvian justice system has undergone reforms for over thirty years. However, key indicators do not seem to have improved. In this article, we attribute this failure to the focus of the reforms, which have primarily centered on the selection of judges and prosecutors, the organization of the justice system, and procedural aspects. Most of these reforms have constituted overarching reforms revisiting previous reforms and offering solutions similar to those already tried, with the hope that —this time— they will be implemented effectively. Based on this, we propose that justice system reform should incorporate an economic or market perspective to better align the incentives of judges and prosecutors with those of society.